2014
DOI: 10.1086/674849
|View full text |Cite
|
Sign up to set email alerts
|

Automated Alerts Coupled with Antimicrobial Stewardship Intervention Lead to Decreases in Length of Stay in Patients with Gram-Negative Bacteremia

Abstract: Active alerting coupled with stewardship intervention in patients with gram-negative bacteremia positively impacted time to appropriate therapy, length of stay, and mortality and should be a target of antimicrobial stewardship programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
1
27
0
2
Order By: Relevance
“…Compared to other studies that have used simulated samples, proposed theoretical benefits from antimicrobial interventions, and/or excluded polymicrobial cultures, this study aimed to provide a practical reference for the effects of this technology on laboratory turnaround times and patient care in a real-world hospital setting (16)(17)(18)(19)(20)(21)(22). While others have bundled rapid bloodstream infection diagnostics with improved stewardship practices for their analyses (9,17), it has been shown that antimicrobial stewardship interventions for Gram-negative bacteremia alone can improve outcomes (23). From a laboratory perspective, it was encouraging that our data demonstrated a positive clinical impact based on the BC-GN test with the antimicrobial stewardship practices that were already in place.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies that have used simulated samples, proposed theoretical benefits from antimicrobial interventions, and/or excluded polymicrobial cultures, this study aimed to provide a practical reference for the effects of this technology on laboratory turnaround times and patient care in a real-world hospital setting (16)(17)(18)(19)(20)(21)(22). While others have bundled rapid bloodstream infection diagnostics with improved stewardship practices for their analyses (9,17), it has been shown that antimicrobial stewardship interventions for Gram-negative bacteremia alone can improve outcomes (23). From a laboratory perspective, it was encouraging that our data demonstrated a positive clinical impact based on the BC-GN test with the antimicrobial stewardship practices that were already in place.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the beneficial aspects of clinical decision support tools have been documented in the literature as well. [14][15][16] …”
Section: Discussionmentioning
confidence: 99%
“…Future research should explore how leaders and staff at microbiology laboratories perceive the interaction with clinicians, as a basis for possible interventions on these lines of communication. Furthermore, studies show that antimicrobial stewardship teams can decrease time to appropriate therapy by close follow up of microbiological test results [30, 31], so establishing such teams in Norwegian hospitals is highly relevant.…”
Section: Discussionmentioning
confidence: 99%